2012
DOI: 10.1097/psy.0b013e3182688e8b
|View full text |Cite
|
Sign up to set email alerts
|

Somatoform Pain

Abstract: Somatoform pain is a highly prevalent, debilitating condition and a tremendous public health problem. Effective treatments for somatoform pain are urgently needed. The etiology of this condition is, however, still unknown. On the basis of a review of recent basic and clinical research, we propose one potential mechanisms of symptom formation in somatoform pain and a developmental theory of its pathogenesis. The emerging evidence from animal and human studies in developmental neurobiology, cognitive-affective n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(28 citation statements)
references
References 127 publications
(129 reference statements)
1
27
0
Order By: Relevance
“…Importantly, our results do not imply that there is no functional relationship between pain and rejection, or that one cannot influence the other. In fact, such interactions may underlie, for example, the increased rate of pain disorders observed following emotional trauma 58 . Developing and using fMRI pattern-based markers that are sensitive and specific to different psychological experiences will provide new leverage points for examining their underlying neural processes, the regulatory effects on the processes, and inter-relationships among different psychological processes.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, our results do not imply that there is no functional relationship between pain and rejection, or that one cannot influence the other. In fact, such interactions may underlie, for example, the increased rate of pain disorders observed following emotional trauma 58 . Developing and using fMRI pattern-based markers that are sensitive and specific to different psychological experiences will provide new leverage points for examining their underlying neural processes, the regulatory effects on the processes, and inter-relationships among different psychological processes.…”
Section: Discussionmentioning
confidence: 99%
“…There is quite a consensus on the role of interpersonal interactions, attachment and trauma history in dysregulated affect of SSD that is linked to alterations in the endocrine, immune, and pain regulating systems ( Henningsen, 2003 ; Luyten et al, 2013 ). Lending support to this linkage, a shared neural system for social pain, such as rejection, exclusion or loss, and physical pain is acknowledged ( Kross et al, 2011 ; Eisenberger, 2012 ; Landa et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Disruptions in specifically interpersonal versus non-interpersonal aspects of experience have substantial psychophysiological effects in animals and humans as well as important long-lasting consequences for physical and mental health (Britton, Taylor, Berridge, Mikels, & Liberzon, 2006; Chiang, Eisenberger, Seeman, & Taylor, 2012; Eisenberger & Cole, 2012; Hofer, 2009; Landa, Peterson, & Fallon, 2012; Slavich, Way, Eisenberger, & Taylor, 2010; Taylor, Eisenberger, Saxbe, Lehman, & Lieberman, 2006). Prior brain imaging studies identified neural circuits that support social cognition (Van Overwalle, 2009).…”
mentioning
confidence: 99%